Does Really One in Ten Believe Capital Punishment Exists in a Contemporary European Community Country? An Endorsed, Prereviewed, Preregistered Replication Study and Meta-Analysis - Boch, Magdalena; Tran, Ulrich S.; Voracek, Martin (Frontiers in Psychology, 2019)
Background: Till et al. (2016) reported that in an Austrian sample approximately one in ten respondents incorrectly believed that Austria still practices, or recently practiced, the death penalty, and that there is a positive association between the amount of weekly television viewing and this gross misperception of the Austrian justice system. Methods: An endorsed, prereviewed, preregistered close replication attempt (N = 597) served to test the veracity of these reported effects. This was coupled with an conceptual extension part, which (a) investigated the potential influence of watching American crime series, (b) accounted for further possible confounds, and (c) tested the generalizability of the effect of television viewing to online streaming. Results: Online survey data (N = 597) replicated the one-in-ten prevalence of incorrect answers with the 5-item death penalty questionnaire used in the original study, but not, when asking directly about Austria’s death penalty practices (prevalence: 0.3%). Younger age, but not the amount of television viewing or online streaming, suggestibility, or preferred TV genre turned consistently predicted incorrect answers in the death penalty questionnaire. Incorrect answers were Mokken-scalable (i.e., formed a common scale, complying with a nonparametric item response model) and were highly consistent. In contrast to the replication study results, a small meta-analysis of all available evidence (3 studies, including the present replication) suggested that the aggregate effect of television viewing nominally was significant, albeit small. Conclusion: The replication study yielded mixed results, which indicate a high prevalence of beliefs that there is capital punishment in a country without death penalty probably is due to a faultily designed questionnaire and thus a research artifact. Also, positive associations of television viewing with such beliefs likely are only small at best.